An evaluation of compliance with the cigarettes and other tobacco products act 2003 in Koppal district, Karnataka - Mane, Vijaykumar P.; Yenkanaik, Yuvaraj Bhanot; Dhanapur, Shankrappa; Yallammanavar, Sangappa; Sreenivasamurthy, Rashmi (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco is a major risk factor for a number of diseases affecting all age groups. One person dies every six seconds due to tobacco use and up to half of current users will eventually die of a tobacco-related disease. Government of India has enacted cigarette and other tobacco products act (COTPA) in the year 2003 to control tobacco use. The objective of study was to estimate the level of compliance to selected sections (4 to 9) of COTPA (cigarette and other tobacco products – prohibition of advertisement and regulation of trade and commerce, production, supply and distribution) act, 2003 in Koppal district, Karnataka. Methods: The present study was a cross sectional study conducted as an independent evaluation of COTPA act 2003 in Koppal district as per National Tobacco Control Program guidelines. Cluster sampling technique was used for sample selection and sample consisted of 158 public places, 102 educational institutional, 87 shops/ sell points and 60 tobacco products. Data entry and analysis was done using microsoft office excel 2013. Results: The prevalence of compliance to section 4, 5, 6A, 6B, 7, 8 and 9 of COTPA act 2003 in Koppal district were 80.3%, 96.5%, 98.9%, 64.8%, 53.3%, 63.3% and 50% respectively. Conclusions: Compliance level was poor especially in relation to display of health warnings on tobacco products which needs to be tackled through strict enforcement of the existing laws.